The Chronic Health Effects of Work-Related Stressors Experienced by Police Communications Workers - Rodolfo A. Perez; Katelyn K. Jetelina; Jennifer M. Reingle Gonzalez (Elsevier, 2021)
Background: Law enforcement communications (i.e., 911 dispatch and call takers) is a challenging and stressful occupation. The purpose of this study is to identify the main stressors associated with employment in law enforcement communications, and to identify and provide context to how these stressors affect workers' health and wellbeing. Methods: This research study included focus groups with 23 call takers and 911 dispatchers employed by a large, urban law enforcement agency in 2018. Thematic analyses were conducted to identify trends. Results: Four themes of stressors emerged (i.e., the high stakes nature of some 911 calls for service, understaffing, supervisor-related stress, and recruiting practice). Two health-related themes emerged as being occupation-related: weight gain and poor sleep patterns/insufficient sleep). Specifically, participants reported negative eating habits resulting in weight gain and obesity, lack of sleep and irregular sleep schedules, and development of hypertension and/or diabetes since beginning their jobs. Conclusion: Law enforcement communications professionals experience a number of the same stressors facing law enforcement officers in patrol. These stressors, combined with the sedentary nature of the job, could result in long-term, chronic health problems.